2012
DOI: 10.5812/cardiovascmed.4601
|View full text |Cite
|
Sign up to set email alerts
|

Pericardial effusion after pediatric cardiac surgeries: a single center observation

Abstract: Background:Development of fibrinous pericarditis after pericardiotomy is a well-recognized reaction. Within a few post-operative days, the inflammated surface of pericardium begins to fuse to the overlying sternum.Objectives:Our aim was to assess the prevalence, risk factors, time course and therapy response of pericardial effusion (PE) after cardiac surgeries in children.Patients and Methods:PE occurrence was assessed prospectively in 486 children who underwent cardiac surgery for congenital heart diseases by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 9 publications
(9 reference statements)
1
20
0
Order By: Relevance
“…However, also some contradictions were found, since in this study no effect of gender or diagnosis severity could be identified and higher thoracic drain production, anticoagulation use, or longer intensive care stay did not seem to convey any additional risk [7, 8, 16]. In addition, this study identified cardiopulmonary bypass use and right-sided heart defects as new risk factors for crPE in children.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…However, also some contradictions were found, since in this study no effect of gender or diagnosis severity could be identified and higher thoracic drain production, anticoagulation use, or longer intensive care stay did not seem to convey any additional risk [7, 8, 16]. In addition, this study identified cardiopulmonary bypass use and right-sided heart defects as new risk factors for crPE in children.…”
Section: Discussionmentioning
confidence: 67%
“…Furthermore, higher pericardial drain production postoperatively and the use of anticoagulation were identified as a risk factor for PE after pediatric cardiac surgery [7, 8]. …”
Section: Introductionmentioning
confidence: 99%
“…Still, it would be of interest to assess the reasons for a longer LOS and if it is related with a better preparation of the patient and the family. Another explanation is the natural timeline of complications after CHD surgery, namely the fact that pleural [13] and pericardial [14] [15] effusions usually occur within two weeks of surgery. Thus, patients who remain in hospital for 14 days can have their complications treated within the same hospital stay, whereas patients discharged earlier need to be readmitted for the management of their post-operative complication.…”
Section: Readmission Ratesmentioning
confidence: 99%
“…The incidence of PE was reported 10%–13.6% for all cardiac surgeries in the recent studies. [ 36 37 ] PE occurs most commonly after corrective cardiac surgeries but may be observed in all types of surgeries involving the pericardial sac. [ 38 39 ] It contributes to postoperative morbidity and mortality, hence to be a risk for hemodynamic compromise.…”
Section: Linical a Pplications Of mentioning
confidence: 99%